Analysis of hepatitis C virus resistance to silibinin in vitro and in vivo points to a novel mechanism involving nonstructural protein 4B. Issue 3 (7th February 2013) - Esser‐Nobis, Katharina; Romero‐Brey, Inés; Ganten, Tom M.; Gouttenoire, Jérôme; Harak, Christian; Klein, Rahel; Schemmer, Peter; Binder, Marco; Schnitzler, Paul; Moradpour, Darius; Bartenschlager, Ralf; Polyak, Stephen J.; et al.
Abstract: Intravenous silibinin (SIL) is an approved therapeutic that has recently been applied to patients with chronic hepatitis C, successfully clearing hepatitis C virus (HCV) infection in some patients even in monotherapy. Previous studies suggested multiple antiviral mechanisms of SIL; however, the dominant mode of action has not been determined. We first analyzed the impact of SIL on replication of subgenomic replicons from different HCV genotypes in vitro and found a strong inhibition of RNA replication for genotype 1a and genotype 1b. In contrast, RNA replication and infection of genotype 2a were minimally affected by SIL. To identify the viral target of SIL we analyzed resistance to SIL in vitro and in vivo . Selection for drug resistance in cell culture identified a mutation in HCV nonstructural protein (NS) 4B conferring partial resistance to SIL. This was corroborated by sequence analyses of HCV from a liver transplant recipient experiencing viral breakthrough under SIL monotherapy. Again, we identified distinct mutations affecting highly conserved amino acid residues within NS4B, which mediated phenotypic SIL resistance also in vitro . Analyses of chimeric viral genomes suggest that SIL might target an interaction between NS4B and NS3/4A. Ultrastructural studies revealed changes in the morphology of viral membrane alterations upon SIL treatment of a susceptible genotype 1b isolate, but not of a resistant NS4B mutant or genotype 2a, indicating that SIL might interfere with the formation of HCV replication sites. Conclusion: Mutations conferring partial resistance to SIL treatment in vivo and in cell culture argue for a mechanism involving NS4B. This novel mode of action renders SIL an attractive candidate for combination therapies with other directly acting antiviral drugs, particularly in difficult‐to‐treat patient cohorts. (HEPATOLOGY 2013)